2019
DOI: 10.5194/cp-15-1913-2019
|View full text |Cite
|
Sign up to set email alerts
|

Water isotopes – climate relationships for the mid-Holocene and preindustrial period simulated with an isotope-enabled version of MPI-ESM

Abstract: Abstract. We present here the first results, for the preindustrial and mid-Holocene climatological periods, of the newly developed isotope-enhanced version of the fully coupled Earth system model MPI-ESM, called hereafter MPI-ESM-wiso. The water stable isotopes H216O, H218O and HDO have been implemented into all components of the coupled model setup. The mid-Holocene provides the opportunity to evaluate the model response to changes in the seasonal and latitudinal distribution of insolation induced by differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
108
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(125 citation statements)
references
References 110 publications
13
108
4
Order By: Relevance
“…Particularly valuable would be transient simulations that include water isotopes as prognostic variables, which allow for direct assimilation of water isotope ratios (Steiger et al, 2017;Okazaki and Yoshimura, 2017), rather than the use of an explicit proxy system model between temperature and δ 18 O. Recent work shows significant improvements to the realism of water-isotope enabled models in the polar regions (Nusbaumer et al, 2017;Dütsch et al, 2019;Cauquoin et al, 2019;Okazaki and Yoshimura, 2019), and longer simulations, once available, should allow us to further improve upon the results we have presented here. In principle, our…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly valuable would be transient simulations that include water isotopes as prognostic variables, which allow for direct assimilation of water isotope ratios (Steiger et al, 2017;Okazaki and Yoshimura, 2017), rather than the use of an explicit proxy system model between temperature and δ 18 O. Recent work shows significant improvements to the realism of water-isotope enabled models in the polar regions (Nusbaumer et al, 2017;Dütsch et al, 2019;Cauquoin et al, 2019;Okazaki and Yoshimura, 2019), and longer simulations, once available, should allow us to further improve upon the results we have presented here. In principle, our…”
Section: Discussionmentioning
confidence: 99%
“…Borehole thermometry at the GISP2 and GRIP sites shows that for the low-frequency changes associated with the last glacialinterglacial transition, the temporal slope is less than half the modern, spatial slope (Cuffey and Clow, 1997;Jouzel et al, 1997). Numerous studies have suggested that precipitation seasonality is the largest source of nonlinearity in the δ 18 O-T site relationship (e.g., Steig et al, 1994;Pausata and Löfverström, 2015); changes in precipitation seasonality are thought to be the primary reason that the effective δ 18 O-T site relationship for the glacial-interglacial transition has such a low slope (Werner et al, 2000;Gierz et al, 2017;Cauquoin et al, 2019).…”
Section: Proxy System Model: δ 18 Omentioning
confidence: 99%
“…Alternatively, their effects must be parameterized as in current state-of-the-art general circulation models, where the typical horizontal resolutions of the ocean component is about 1 • . Practically, given the present high-performance computer capacities, efficient and parallelized model codes, it is now possible to conduct isotope-enabled (e.g., Cauquoin et al, 2019;Werner et al, 2018) simulations for 50-100 model years per day even with a multiscale ansatz (Shi et al, 2020).…”
Section: 1029/2019pa003782mentioning
confidence: 99%
“…Further, many speleothem records come from these regions, and historically, model simulations have had difficulty capturing the speleothem‐suggested δ 18 O responses (Battisti et al, 2014; Comas‐Bru et al, 2019; Liu, Wen, et al, 2014; Liu & Battisti, 2015; Tabor et al, 2018). Although recent water isotopologue modeling work appears to have somewhat better model‐proxy agreement in East Asia, possibly due to the inclusion of dynamic vegetation (Cauquoin et al, 2019). We define monsoon regions as gridcells where >50% of total precipitation falls during the wet season (NDJFM for the SAM and MJJAS for the AM) and wet season minus dry season precipitation is >2 mm/day, similar to the definition presented in Wang et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Climate models with water isotopologue tracking have been developed to allow for more direct comparison between models and proxies. Despite providing some refined interpretations, water isotopologue tracking‐enabled models also have difficulty capturing the amplitude of the δ 18 O spel response with changes in summer insolation, suggesting that the simulated hydrologic response bias is not entirely a result of incorrect proxy interpretation (Battisti et al, 2014; Cauquoin et al, 2019; Comas‐Bru et al, 2019; Liu, Wen, et al, 2014; Tabor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%